(untitled) (Castilla. Estudios de Literatura, 2024)
This article focuses on the recreation of fictions and the phenomenon of fanfiction in the field of Literature to observe the creative processes and the transformative nature of fanfiction writing and the decisive role of readers in the construction of possible worlds.